PENGELOLAAN PERPUSTAKAAN YANG BAIK MENDUKUNG PROSES PEMBELAJARAN YANG EFEKTIF DAN EFISIEN - Bajongga Silaban; Januaris Pane (Bajang Institute, 2022)
The library is the heart of a school which has a very vital function in supporting the learning process. Therefore, the school library with the ranks of librarians in it, has an obligation to